Quick Response Code-based Pop-Up Book Media: Plant Reproduction Systems Topic for Grade VI Elementary School - Putu Wulan Libriani; I Made Suarjana; Gede Wira Bayu (Journal of Education Technology, 2023)
The use of innovative learning media based on digital technology can have a positive impact on improving the quality of the learning process. This study aims to develop a media pop-up book based on a quick response code on the topic of plant propagation that has been tested for validity. This research was conducted through five stages in the ADDIE model. This research was only carried out until the development stage. Data collection was carried out using a questionnaire method. The assessment instrument used to test the validity of the pop-up book media in this study was a rating scale with a learning media assessment sheet. The subject of this study was pop-up book media based on quick response code on the topic of plant reproduction systems for grade VI elementary schools with the validity of the media as a research object. The assessment was carried out by four experts consisting of two lecturers and two sixth grade teachers. The results of the assessment are then averaged to determine the validity of the pop-up book media based on the quick response code that has been made. From the results of the assessment by four experts, an average media validity score of 93% was obtained, the material validity average score was 96% and the media validity by practitioners was an average of 98% with very good qualifications. Based on these results, it can be concluded that the pop-up book media based on the quick response code on the topic of plant reproductive systems for grade VI elementary schools is valid in the very good category.